Performance Measurement of Outbound Logistics in the Fertilizer Industry for Distribution Activities Based on Performance Of Activity (POA) Model and Analytical Hierarchy Process(AHP) Method - Della Afi Rizky Anggraini; Farida Pulansari; Nur Rahmawati (Science and Technology Research Centre Universitas PGRI Semarang, 2024)
This research presents problems in the fertilizer industry with the goal of knowing the performance of fertilizer distribution. The outbound logistics process in fertilizer distribution activities is important, because it is connected to the process of delivering fertilizer products to consumers. However, in carrying out fertilizer distribution activities, there are problems that occur due to the mismatch of warehouse capacity over storage and differences in estimated delivery time. This situation results in missed fertilizer supplies for consumers. This research uses KPI criteria based on the Performance Of Activity (POA) model and performance weighting with the Analytical Hierarchy Process (AHP) method to determine the value of the Company's outbound logistics performance. The discussion with company experts resulted in 12 KPI indicators based on POA criteria consisting of cost, time, capacity, capability, productivity, utility, and outcome. After weighting with the AHP method, the total outbound logistics performance of 85,918 is included in the good category and can still be improved in the excellent category by giving recommendations for improvement. So, further research can be made collaborating the AHP method with other methods such as the SCOR method to simplify the selection of supply chain process activities or using the Fuzzy AHP method to reduce the subjectivity of the research.